The legal meaning of state custodianship in the context of the Mineral and Petroleum Resources Development Act 28 of 2002 - Schmidt, Hendrik (Department of Private Law, 2023)
The Mineral and Petroleum Resources Development Act, 2002 introduces a new mineral and petroleum law dispensation in South Africa. The introduction of the new dispensation follows the first democratic election in 1994 that required a reconsideration of the role of the state in the allocation and exploitation of mineral and petroleum resources. The state's right to sovereignty is realised by introducing the principle of state custodianship. Whilst the MPRDA does not define state custodianship, the courts have been hesitant in providing an interpretation. Historically, the majority of South Africans were excluded from the allocation and exploitation of mineral and petroleum resources caused by racial practices. The notion of state custodianship brings substantive changes to the regulation of mineral and petroleum resources. The state as custodian is responsible for regulating the nation's mineral and petroleum resources in accordance with the objectives determined by the MPRDA. As regulator, the state has been allocated increased control over prospecting and mining activities. This increased control must enhance the transformative goals of the new mineral and petroleum law dispensation whilst simultaneously considering the role of mineral and petroleum resources in the economic development of the country. In accordance with its responsibilities imposed in terms of the Constitution, the state must ensure that everyone benefits from mineral and petroleum exploitation. Such responsibilities must be exercised within the Constitutional imperative to avoid or minimize environmental harm The state as custodian owes a fiduciary duty towards the nation in respect of the minerals and petroleum resources. This fiduciary duty exists between the state and its citizens. The state must exercise its duty to the standard required of a fiduciary with regards to the property entrusted to it to regulate. Due to the nature of the concept of custodianship, the state is not the owner of mineral and petroleum resources. Whilst the landowner, and in certain instances the mineral rights holder, before the adoption of the MPRDA determined access to minerals, the state as custodian is now responsible for determining access to minerals. The joint interests of the South African nation as a whole is to be promoted by the state in its role as custodian. The public interest of access to and use of the mineral and petroleum resources determined by the MPRDA, and the Constitution must be safeguarded. The implementation of the object of equitable access to minerals is dependent on the state as custodian. The transformative role of the state is enhanced by the shifting of the basis of mineral law to public law. The administering of a state controlled mineral law system has led to the responsibilities of state custodianship having to be exercised within a public law environment. The interpretation of the state's duties as custodian is dependent on various considerations, some of them being the provisions of the MPRDA, the application of the principles of administrative law and the fiduciary nature of state custodianship.